Sociological Study of the Role of Lifestyle in the Quality of Life of Citizens 65 Years and Older in Bandar Mahshahr - Masoud Ganji; Reza Ali Mohseni; Mansour Sharifi; Ali Reza Kaldi; Hassan Malek (توسعه اجتماعی)
Today, one of the concerns is a Quality Lifestyle. This article examines the Sociological role of Lifestyle in the Quality of Life of Citizens over 65 years of age in Bandar Mahshahr. The paper is based on the Scandinavian-American approaches and the social quality approach to quality of life and the combined view of Bourdieu's theories from the field in the theory of differentiation, and Giddens's definition of lifestyle and social construction to lifestyle, by survey method. The present article has been done by Survey Method among the Statistical Population of Citizens 65 years and older in Bandar Mahshahr city. 396 citizens aged 65 and over have been identified as a Statistical Sample using the Cochran's formula, Statistical Data were collected through Stratified Sampling and Researcher-made Questionnaire tools and finally analyzed using SPSS Statistical Software and Descriptive and Inferential Statistical tests. The results show that the Objective, Subjective and Social Quality of Life of Citizens respectively, was at the level of 61.69, 52.3 and 41.2% of the maximum potential percentage of these dimensions of Quality of Life. Research results show; the Lifestyle of Citizens is more Consumption than Productive and on the other hand is Social rather than Economic and Cultural. According to the results, Economic Lifestyle with 0.485 Total Impact, Social Lifestyle with 0.375 Total Impact, Cultural Lifestyle with 0.280 Total Impact on the one hand and Productive Lifestyle with 0.558 Total Impact and Consumption Lifestyle with 0.450 Total Impact, respectively, had the greatest impact on Quality of Life. If the Quality of Life as a whole is targeted; Respectively, there is a need for a Combination of Economic, Social and Cultural Actions and Lifestyles, which a) Triple Economic, Social and Cultural Capitals and b: comparative perception, evaluation and Subjective Perceptions of the Triple Capitals that can be Called that Subjective Capital; Which together form the four Economic, Social, Cultural and Subjective Capitals, respectively; Produce. This Quality of Life can be called Action-Oriented or Interactive Quality of Life.